2010
DOI: 10.1007/s11145-010-9258-7
|View full text |Cite|
|
Sign up to set email alerts
|

Cognitive profiles of poor readers of Kannada

Abstract: The alphasyllabary of Kannada comprises more than 400 symbols called akshara; each symbol is visuo-spatially complex with a consistent representation at the dual levels of the syllable and the phoneme. We investigated reading difficulties in Kannada among 8-12 year old children by conducting a between-groups followed by a case series analysis. We compared the children with reading difficulties with same age competent readers and younger readers who were similar in language level, matched on measures of vocabul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 39 publications
3
31
0
Order By: Relevance
“…To our knowledge, this is the first study to examine both grammatical and phonological encoding in sentence repetition and the pattern of associations between these and cognitive–linguistic measures such as vocabulary knowledge and nonword repetition within a model of the language production system. The findings provide support for growing evidence that the entire language system is recruited during sentence repetition while being sensitive to language-specific characteristics (e.g., inflections in Kannada: Nag & Snowling, 2011; prepositions in English: Moll et al, 2013). Other studies have shown that the task has been sensitive to subtle individual differences, particularly to variations at the lower end of the distribution (e.g., English: Conti-Ramsden et al, 2001; Redmond et al, 2011; Rice et al, 2005; Dutch: Wilsenach 2006).…”
Section: Discussionsupporting
confidence: 68%
“…To our knowledge, this is the first study to examine both grammatical and phonological encoding in sentence repetition and the pattern of associations between these and cognitive–linguistic measures such as vocabulary knowledge and nonword repetition within a model of the language production system. The findings provide support for growing evidence that the entire language system is recruited during sentence repetition while being sensitive to language-specific characteristics (e.g., inflections in Kannada: Nag & Snowling, 2011; prepositions in English: Moll et al, 2013). Other studies have shown that the task has been sensitive to subtle individual differences, particularly to variations at the lower end of the distribution (e.g., English: Conti-Ramsden et al, 2001; Redmond et al, 2011; Rice et al, 2005; Dutch: Wilsenach 2006).…”
Section: Discussionsupporting
confidence: 68%
“…Nag and Snowling (2011) in their study also noted that phonemic manipulation was the only variable that could significantly differentiate between poor and normal Kannada readers when assessed on different phonological processing skills. In addition to phonemic awareness, akshara knowledge is seen to be significantly related to reading accuracy in many alphasyllabic languages such as in the Bengali (Nag & Sircar, 2008) and with the overall reading skills in Kannada (Nag, 2007;Nag & Snowling, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Phonemic awareness more specifically has been shown to be a good predictor of reading skill (Hulme et al, 2002; Snowling, 1981). Phonological deficits are also thought to be a primary deficit in reading disorders of alphasyllabic writing systems (Nag & Snowling, 2011), but children with poorer visual processing skills are also at heightened risk for poor reading achievement. The contrast is even more marked in the Chinese writing system, which uses a logographic mapping principle.…”
Section: Introductionmentioning
confidence: 99%